Posttraumatic Stress Disorder and Alcohol Use Disorder: A Critical Review of Pharmacologic Treatments. (19th January 2017) - Petrakis, Ismene L.; Simpson, Tracy L.
Abstract : Treatment of alcohol use disorder (AUD) is complicated by the presence of psychiatric comorbidity including posttraumatic stress disorder (PTSD). This is a critical review of the literature to date on pharmacotherapy treatments of AUD and PTSD. A systematic literature search using PubMed MESH terms for alcohol and substance use disorders, PTSD, and treatment was undertaken to identify relevant randomized controlled trials (RCTs). The studies were independently evaluated (ILP and TLS) and those that evaluated the efficacy of a pharmacotherapy for individuals diagnosed with AUD and PTSD and were RCTs were selected. Studies were grouped in 3 categories: (i) those that evaluated first‐line treatments for PTSD, (ii) those that evaluated medications to target AUD, and (iii) those that evaluated medications hypothesized to be effective in targeting alcohol consumption as well as PTSD symptoms. Nine RCTs were identified; 3 focused on medications to treat PTSD, 4 focused on AUD, and 3 to target both. One study included both a medication to treat PTSD and 1 to treat AUD so was discussed twice. All but 1 of the studies found that PTSD symptoms and drinking outcomes improved significantly over time. There is not 1 agent with clear evidence of efficacy in this comorbid group. The results for medications to treat PTSD are inconclusive because of contradictory results. There was weak evidence to support the use of medications to treat AUD among those with comorbidity with PTSD. Findings for medications that were hypothesized to treat both disorders were also contradictory. Most studies provided a combination of interventions to treat both disorders. Despite the contradictory results, this review suggests that individuals with AUD and comorbid PTSD can safely be prescribed medications used in noncomorbid populations and patients improve with treatment. Abstract : This is a critical review of the literature to date on pharmacotherapy treatments of alcohol use disorders (AUD) and posttraumatic stress disorder (PTSD). Relevant studies included those evaluating (i) treatments for PTSD, (ii) medications for AUD and (iii) medications targeting both. Most studies found that PTSD symptoms and drinking outcomes improved significantly over time. While there are some contradictory results, individuals with AUD and comorbid PTSD can safely be prescribed medications used in non‐comorbid populations and patients improve with treatment.